"Investigating the factors affecting brain drain in Greece: looking beyond the obvious". Issue 3 (6th May 2020) - Panagiotakopoulos, Antonios
Abstract : Purpose: The study explores the reasons why talented people leave Greece and go abroad using a qualitative approach to data collection in order to get a deep understanding on the actual reasons of brain drain in Greece, which affects the sustainability of domestic businesses and the overall economic development of the country. Design/methodology/approach: A qualitative approach was adopted consisting of 80 interviews with business and IT professionals, healthcare professionals and academics of various disciplines that live and work in the United Kingdom, Germany, United States and Australia. Data were collected over a three-year period (May 2015–May 2018). Findings: The results showed that the vast majority of respondents decided to leave their home country due to the prevalent cultural mindset of most Greek citizens, government policymakers and employers in Greece. In particular, 65% of respondents decided to live and work abroad due to the deep crisis of social values in the country and the high political corruption, while just 35% pointed to purely financial and other work-related reasons (e.g. low salaries, poor working conditions, no employment prospects, lack of job security) as the key ones for leaving the country. Essentially, the respondents argued that the individualist cultural values that have been predominant in the Greek society for years now have become evident in political action causing several problems such as social injustice and poverty. Research limitations/implications: The findings have important implications both for those who hold governmental posts and the remaining citizens of Greece. Both government officials and citizens should re-examine their roles, values and ideals. The blame for the extensive brain drain in the country cannot be put only on the political parties that ruled the country during the last decades; the people who elected them are also responsible. The country seems to remain trapped in a crisis of social values that parents and the formal education system in Greece have cultivated for years now. In that respect, formal education in the country should be transformed radically in order to act as an important agency inculcating the new generations with a sense of duty in shaping a democratic political culture that emphasizes equality and condemns egalitarian practices. Originality/value: The scant evidence around this topic is based on quantitative research that fails to explore in much depth the reasons of brain drain in the country. Previous studies revealed that the phenomenon of brain drain in Greece has been predominantly caused by the poor financial performance of the country during the last decade. This has been further supported by the claims of several policymakers who argue that the Greek crisis has been a fiscal one. However, the present study sheds new light and unmasks the root cause of brain drain in Greece stressing that the country essentially faces a crisis of values and a corrupted civic culture.